Efforts to Combat Criminal Acts of Unlicensed Cosmetics Distribution in Makassar City - Sutiawati; Jasmaniar (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
This empirical legal research aims to investigate the causes of crimes related to the circulation of cosmetics without distribution permits in Makassar City and propose countermeasures. Conducted at the Sub Directorate 1 of Trade Industry of the Special Criminal Investigation Directorate of South Sulawesi Police and the Makassar Food and Drug Monitoring Center (BPOM), the study utilizes primary data gathered through informant interviews and secondary data from various sources like laws, regulations, and research findings. Factors contributing to these crimes include inadequate supervision, high permit costs, slow processing, aggressive marketing, competitive pricing, and the allure of fast cosmetics. Countermeasures involve Pre-Emptive, Preventive, and Repressive strategies. However, obstacles such as insufficient witness participation, difficulty accessing expert assistance, limited investigator resources, budget constraints, and inadequate infrastructure hinder these efforts.